إدارة الطلب على المياه وفق مؤشرات الكفاءة - خدام, منذر; حسن, إبراهيم علي (Latakia University Journal -Biological Sciences Series, 2013)
تعاني سورية من عوز مائي شديد سوف يتفاقم في المستقبل، وذلك بسبب محدودية مواردها المائية، وزيادة الطلب على المياه، خصوصاً في الزراعة. تقدر الموارد المائية السورية المتاحة من مختلف المصادر بنحو 14.6 مليار م3، في حين قدر الطلب على المياه في عام 2010بنحو 14.09 مليار م3، سوف يرتفع إلى نحو 17 مليار م3 في عام 2020 مسجلاً فجوة مائية تقدر بنحو 5 مليار م3. ومن أجل ردم هذه الفجوة كان لا بد من التوجه نحو إدارة الطلب على المياه وفق معايير الكفاءة، وترشيد استعمالات المياه. وبالفعل فقد بينت نتائج البحث أن الري بالتنقيط يحقق وفراً في كميات المياه المستخدمة للهكتار الواحد تصل إلى أكثر من 50%، محققاً كفاءة تصل إلى 85% بالمقارنة مع59% كفاءة للري بالغمر . Syria suffers from severe water deficiency that will worsen in the future due to limited water resources and increasing demand for water, especially in agriculture. Syrian water resources, available from various sources, are estimated by 14.6 billion cubic kilometers, while the estimated demand for water in 2010 was about 14.09 billion cubic meters, it will rise to about 17 billion cubic meters in 2020 recording a water gap estimated at 5 billion cubic meters. In order to bridge this gap it was necessary to work on managing the demand on water according to the criteria of efficiency and rationalization of the use of water. Indeed, results showed that drip irrigation saves a proportion in the amount of water used per hectare up to more than 50%, achieving efficiency up to 85% compared with 59% efficiency for flood irrigation.